Old Institutionalism Vs. Mainstream Economics: An Intellectual - Mahmoud Mashhadi-Ahmad (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2015)
In the arena of Economic thought, there has always been some intellectual confrontation between the two major economic schools, i.e. Institutionalism and Neoclassical economics. This challenge has taken place at different levels; ranging from the most fundamental levels which are principles of ontology and epistemology to higher levels of policy implications. This article is an attempt to address some of the aspects of this debate and the challenges created by it. Neoclassical advocates claim that institutionalism suffers from lack of theory. Indeed, they try to nullify institutionalism as non-scientific school. But, suddenly these questions arise that "what is science, and what can be considered as science at all?" "Is neoclassical economics science and institutional economics not?" These questions are among the issues which are addressed in this article. It will be shown in this article that institutionalism has an important core of economic theories that turns it to a powerful paradigm. But, in order to understand this, we have to go beyond what is considered theory in neoclassical school. Furthermore we will go through other claims that these two schools hold against each other and address some of them such as realism, scope and precision of theory, and solidarity of paradigm. We will show that in some of these areas such as perception of reality and realism, the difference between these two schools of thought is essential.